Paleoclimatic studies from the tree-ring of Himalayan birch from Langtang National park, central Nepal (Journal of Nepal Geological Society, 2013)
Himalayan birch (Betula utilis D Don) is a long live, broadleaf species native to the Himalayas.  However, this species has received limited attention for dendroclimatic studies world widely. In order to investigate the dendrochronolgical potential of this species in the central Himalayas, we analyzed 26 cores from 22 trees collected from Langtang National park, central Nepal, in May 2010. Based on these samples, we developed 371-year chronology extending back to 1639 AD. The chronological statistics, such as mean sensitivity and correlation between tree-ring series showed its high potentiality for the dendroclimatological study. In addition, the radial growth of Himalayan birch records clear climatic signals. Precipitation in May and early summer (March-May) plays a significant role (p